Cortex phellodendri Extract Relaxes Airway Smooth Muscle - Jiang, Qiu-Ju (Evid Based Complement Alternat Med, 2016)
Cortex phellodendri is used to reduce fever and remove dampness and toxin. Berberine is an active ingredient of C. phellodendri. Berberine from Argemone ochroleuca can relax airway smooth muscle (ASM); however, whether the nonberberine component of C. phellodendri has similar relaxant action was unclear. An n-butyl alcohol extract of C. phellodendri (NBAECP, nonberberine component) was prepared, which completely inhibits high K(+)- and acetylcholine- (ACH-) induced precontraction of airway smooth muscle in tracheal rings and lung slices from control and asthmatic mice, respectively. The contraction induced by high K(+) was also blocked by nifedipine, a selective blocker of L-type Ca(2+) channels. The ACH-induced contraction was partially inhibited by nifedipine and pyrazole 3, an inhibitor of TRPC3 and STIM/Orai channels. Taken together, our data demonstrate that NBAECP can relax ASM by inhibiting L-type Ca(2+) channels and TRPC3 and/or STIM/Orai channels, suggesting that NBAECP could be developed to a new drug for relieving bronchospasm.